The European dimension of vocational training and the problems linked to the translation of its terminology : proposal for an English-German-French glossary of vocational training - Ant, Marc [Verfasser] (Centre de Compétences Génie Technique du Bâtiment, 2023)
The publication deals with the problems of translating vocational training terminology and provides recommendations on how terminological development can succeed.
Keywords: 370; Berufsbildung; Glossar; Deutsch; Englisch; Französisch